Lengthening by distraction osteogenesis in congenital shortening of metacarpals - Bulut, Mehmet; Ucar, Bekir Yavuz; Azboy, Ibrahim; Belhan, Oktay; Yilmaz, Erhan; Karakurt, Lokman (Turkish Assoc Orthopaedics Traumatology, 2013)
Objective: The aim of this study was to present the results of seven cases of metacarpal lengthening by distraction osteogenesis and to discuss the ideal daily rate of distraction. Methods: Metacarpal lengthening was performed by distraction osteogenesis in the seven metacarpals of four patients (3 females, 1 male; mean age: 14.9 years). A unilateral external fixator was used for lengthening. Lengthening was initiated with a distraction rate of 2x0.5 mm/day in the patient with bilateral. involvement of the middle and ring metacarpals. On the tenth day of lengthening, distraction was discontinued due to pain and contracture. Then, distraction was continued with a rate of 2x0.25 mm/day. In all other cases, the distraction rate was 0.5 mm/day. Pre- and postoperative range of motion was measured with a goniometer. Patient satisfaction was evaluated with visual analog scale. Results: The mean pre- and postoperative metacarpal lengths were 34.6 pun (range: 33 to 37) and 49.7 mm (range: 47 to 52), respectively. The mean lengthening achieved was 15.1 mm (range: 14 to 17), while the Mean distraction rate was 0.55 mm/day (range: 0.48 to 0.63). No functional loss was observed in the fingers at the final check-up. The patients were happy with the functional and cosmetic results. Conclusion: Distraction osteogenesis is a safe method providing acceptable cosmetic and functional results in patients with congenital metacarpal shortness. The length of metacarpals and muscles that will be affected from lengthening should be considered when determining the daily rate of distraction.
Keywords: Congenitally brachymetacarpia; distraction osteogenesis; external fixator; lengthening